Prognostic Implications of Right Ventricular Remodeling and Function in Patients With Significant Secondary Tricuspid Regurgitation. Issue 10 (3rd September 2019) - Dietz, Marlieke F.; Prihadi, Edgard A.; van der Bijl, Pieter; Goedemans, Laurien; Mertens, Bart J.A.; Gursoy, Erhan; van Genderen, Olton S.; Ajmone Marsan, Nina; Delgado, Victoria; Bax, Jeroen J.
Abstract : Background: In patients with significant (moderate and severe) tricuspid regurgitation (TR), the decision to intervene is influenced by right ventricular (RV) size and function. RV remodeling in significant secondary TR has been underexplored. The aim of this study was to characterize RV remodeling in patients with significant secondary TR and to investigate its prognostic implications. Methods: RV remodeling was characterized by transthoracic echocardiography in 1292 patients with significant secondary TR (median age 71 [62–78]; 50% male). Four patterns of RV remodeling were defined according to the presence of RV dilation (tricuspid annulus≥40 mm) and RV systolic dysfunction (tricuspid annulus systolic excursion plane<17 mm): pattern 1, normal RV size and systolic function; pattern 2, dilated RV with preserved systolic function; pattern 3, normal RV size with systolic dysfunction; and pattern 4, dilated RV systolic dysfunction. The primary end point was all-cause mortality and the event rates were compared across the 4 patterns of RV remodeling. Results: A total of 183 (14%) patients showed pattern 1 RV remodeling; 256 (20%) showed pattern 2; 304 (24%) presented with pattern 3; and 549 (43%) had pattern 4 RV remodeling. Patients with pattern 4 RV remodeling were more frequently male; more often had coronary artery disease, worse renal function, and impaired left ventricular ejection fraction; and were more often symptomatic. Only 98 (8%) patients underwent tricuspid valve annuloplasty during follow-up. During a median follow-up of 34 (interquartile range, 0–60) months, 510 (40%) patients died. The 5-year survival rate was significantly worse in patients presenting with patterns 3 and 4 RV remodeling in comparison with pattern 1 (52% and 49% versus 70%; P =0.002 and P <0.001, respectively), and were independently associated with poor outcome on multivariable analysis. Conclusions: In patients with significant secondary TR, patients with RV systolic dysfunction have worse clinical outcome regardless of the presence of RV dilation. Abstract : Supplemental Digital Content is available in the text.